Perceived Challenges and Coping Mechanism in Transitional Learning on Students’ Performance in TLE - Baccay, Jamelle R; Versano, Dolores D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to determine the perceived challenges and coping mechanisms in transitional learning on students’ performance in TLE based on the achievement test. This employed the descriptive-correlational with the comparative design of quantitative method as participated by 150 Grade Nine (9) respondents in the researcher’s locale, who were chosen using the random sampling procedures. The data were gathered using an evaluation questionnaire and achievement test which are validated with the help of the experts. Data communications were established before data gathering procedures and were analyzed using percentage, mean, weighted mean, standard deviation, Pearson r, and t-test. The respondents were at the level of approaching mastery in TLE 9 competencies. The study’s findings revealed that there was a significant difference in perceived challenges and coping mechanisms in transitional learning and the sex profile of the respondents. However, there is no significant relationship between the perceived challenges and coping mechanisms in transitional learning and TLE performance. The study recommends the enhancement of teaching.